PENERAPAN PENDEKATAN SITUASIONAL UNTUK MENINGKATKAN KEMAMPUAN BELAJAR KOSA KATA SISWA SMPN 10 PONTIANAK - Rizka Damayanti; Ina Ina; Lusi Lusi (Universitas Tanjungpura, 2019)
AbstractVocabularies are the most important component in language; therefore vocabulary learning is necessary because listening, speaking, reading, and writing skills require vocabularies as their foundation. However, in learning vocabularies we often experience these following hurdles and problems; students are less interested with mandarin, little opportunity to speak mandarin, as well as the limited learning materials. Those problems will furthermore affect the students’ learning skills. To improve students’ learning skill and to make it easier for students to learn mandarin, the author gave a pre-test for students of Junior High School 10 class IXB and IXC, followed by teaching them using situational approach, and gave them post –test afterwards. After comparing pre-test and post-test results, we found that situational approach was very efficient in improving students’ learning skill as well as finding an efficient teaching method. Keywords: vocabularies, vocabulary learning, situational approach